Anak Susuan Dalam Hadis Nabi dan Pandangan Ulama - Fitri Sari (Jurnal Penelitian Medan Agama, 2018)
The problem discussed in this paper is how the scholars view the hadith of the Prophet. regarding breastfeeding children, then how much or how many times the child suckles for the emergence of a relationship that will eventually cause the illegitimate marriage of a brother. This study uses the methodology of comparing the opinions of scholars. This study concludes that there are differences of opinion among scholars regarding how much the level of breastfeeding is said to be that the child is a breastfeeding child. First, according to Daud az-Zahiri (fiqh leader of the School of Az-Zahiri) the level of breastfeeding that forbids marriage is at least three times suction, and if it is less than that it is not forbidden for a man to marry the woman where he suckles. According to Syafi'i and Hanbali school scholars, the level of breastfeeding that forbids marriage is five or more times, and carried out separately. Third, according to the Hanafi and Maliki School scholars, the level of abuse that forbids a man from marrying the woman where he is breastfeeding has no strict limits, and what is important is that the sucked milk reaches the stomach of the child, thus providing energy in the growth of the child.